Proceedings of the 2nd International Driving Symposium on Human Factors in Driver Assessment, Training and Vehicle Design: Driv 2005
DOI: 10.17077/drivingassessment.1103
|View full text |Cite
|
Sign up to set email alerts
|

The Dimensions of Driver Performance during Secondary Manual Tasks

Abstract: Summary: This analysis identified the underlying dimensions of driver performance using data obtained from drivers engaged in secondary manual tasks. Randomly chosen subjects balanced for age and gender used one of five advanced navigation and communication systems while driving on a closed roadway. Fifteen driver performance variables were averaged and standardized across subjects for 79 tasks. There were high correlations between all variables. Principal Component Analysis (PCA) found that the vector of load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 1 publication
2
27
0
Order By: Relevance
“…It accomplished this result despite the near collinearity of several of the variables (see Young & Angell, 2003), contrary to conventional statistical wisdom. We believe this result is because the variables selected for the MLR model were based on extensive analysis, and expertise from experienced applied statistical analysts.…”
Section: Model Methods Comparisonmentioning
confidence: 83%
See 3 more Smart Citations
“…It accomplished this result despite the near collinearity of several of the variables (see Young & Angell, 2003), contrary to conventional statistical wisdom. We believe this result is because the variables selected for the MLR model were based on extensive analysis, and expertise from experienced applied statistical analysts.…”
Section: Model Methods Comparisonmentioning
confidence: 83%
“…Ten driver performance variables were measured for the static and dynamic tests (Table 1, see also Angell, et al 2002;Young & Angell, 2003). There were two trials for each task for each participant for tasks in sets 1 and 2.…”
Section: Variables Data Collection and Preliminary Data Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Yet conventional driver workload variables had high lab-to-road correlations for the identical tasks (r > 0.9), suggesting something unusual about event detection variables that warranted further investigation. Young and Angell (2003) did a principal component analysis of a large set of driver performance variable means, for a wide range of visual-manual tasks, using event lights on the hood and side mirror while driving on a closed road. They showed that across tasks, event detection on the road is positively correlated with driver workload variables on the first dimension, but negatively on the second.…”
Section: Static Load Test (Slt)mentioning
confidence: 99%